Implementasi Akad Murabahah di BNU’26 Magelang - Ayyusuf, Imanul Achmad Al Amir; Fitriyani, Yeny; Purwanto, Purwanto; Aini, Qurotul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research focuses on implementing the Murabaha contract in BNU'26 Magelang District, the only community bank in Indonesia. BNU's problems in implementing the concept of pure Sharia are related to the constraints of banking laws prohibiting direct transactions. Therefore, to carry out Murabaha transactions, BNU has to partner with suppliers of goods. The second problem is more customer understanding of the Murabaha contract. This research was conducted at BNU'26 Magelang using a qualitative method. Data was collected through interviews. The results of this study indicate that murabaha financing uses murabaha bil wakalah, where the bank does not provide goods directly. Alternatively, the bank works with other parties to provide goods used as Murabaha financing to customers.